A Billion Little Pieces: RFID and Infrastructures of Identification - Frith (MIT Press, 2019)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing; Fields, Waves and Electromagnetics; Signal Processing and Analysis; Aerospace; Transportation